A case study of feline triaditis - Fadhilah Amaliyah Haq; Arief Purwo Mihardi; Afifah Hasna; Damar Pramesti Kusumarini; Malni Sovinar (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2021)
Triaditis is an inflammatory condition involving three specific organs, namely the pancreas, liver, and intestines. The most common clinical signs of triaditis are vomiting, diarrhea, jaundice, and loss of appetite. Therefore, this case study was con-ducted to determine cases of triaditis in cats with these clinical signs. This case study was carried out on five cats with diar-rhea, lethargy, and loss of appetite. The fecal scores of cats with diarrhea were 2 and 3. Based on physical examination, there were two cats with hepatomegaly and three cats with jaundice on their mucosa. Treatments for five cats with diarrhea were antibiotic combination (sulfadiazine-trimetropine 50 mg/kg BW) and combination of antispasmodic, analgesic, and antipyret-ic (dipyrone-lidocaine 5 mg/kg BW). Treatments for three cats with jaundice were asering fluid therapy and oral medication (ursodeoxycholic acid 8 mg/kg BW). Anthelmintic combination (fenbendazole, praziquantel, and pyrantel pamoate 0.07 g/kg BW) was given as an additional therapy for cats with intestinal worms. The two cats with diarrhea, hepatomegaly and jaun-dice were not survive after about one week of treatment, while the other one can survive until now